WEIGHT LOSS IN PNEUMONIA PATIENTS AGED 6-60 MONTHS TREATED AT CHILDREN’S HOSPITAL 2 AND ITS RELATIONSHIP TO LENGTH OF HOSPITAL STAY AND TREATMENT RESPONSE - Nguyễn Thị , Thu Hậu; Nguyen, Minh Chau; Doan Thi , Ngoc Han; Tran, Quynh Huong; Tran Thi, Thao Suong; Nguyen, Hoang Phong; Doan Thi, Bao Thuy; Nguyen Thi , Tuyet Dung (Tạp chí Dinh dưỡng và Thực phẩm, 2024)
Aims: To determine the rate of weight loss and the relationship between weight loss, length of hospital stay, and treatment response in pneumonia patients aged 6-60 months treated at Children’s Hospital 2 (CH2). Methods: A hospital cross-based prospective study was conducted on 208 patients aged 6-60 months diagnosed with pneumonia and treated as inpatients at the Respiratory Department 1 and 2 of CH2 from March to April 2024. Results: The rates of weight loss after 3 days, after 7 days of hospitalization, and at discharge were 27.6%, 38.1%, and 38.0% respectively. The length of hospital stay for children with weight loss ≥ 5% after 3 days of hospitalization and at discharge was longer than for those with weight loss < 5%, and this difference was statistically significant (p < 0.05). Children with weight loss ≥ 5% after 3 days of hospitalization and at discharge had a poorer treatment response compared to children with weight loss < 5% [(RR (95%CI)= 5.88 (1.71-20.1) and RR (95%CI)= 4.86 (1.95-12.1), respectively (p=0.025 and p=0.001). Conclusion: Regulary monitoring children’s weight during treatment and providing nutritional support to prevent excessive weight loss is essential to improve the treatment process and the hospital stay.